A city-level analysis of the spatial distribution differences of green buildings and the economic forces – A case study in China. (15th October 2022) - Yan, Hui; Fan, Ziyan; Zhang, Yangbing; Zhang, Lei; Hao, Zhibiao
Abstract: The comprehensive development of green buildings is constrained by the regional imbalance distribution in China. Considering the shortness of previous studies at a provincial level in making practical guidance, this paper conducts a city-level study in China based on a panel dataset of Guangdong cities from 2008 to 2019, using a series of difference evaluation indicators to analyze the characteristics of the spatial distribution differences of green buildings and using grey correlation model and panel regression model to explore the influences made by critical economic factors. The results show that the spatial distribution of green building area in Guangdong Province shows a core-periphery structure, presenting a high imbalanced status. However, the imbalance has decreased over time, with the degree of spatial aggregation of green buildings in most cities steadily improving. Resident income, financial support, and real estate market all have significant positive impacts on the spatial aggregation of green buildings, and the construction industry development has a significant negative impact. As such, concrete suggestions on the above four aspects have been given to reduce the spatial distribution differences of green buildings between different cities, which can guide the balanced development of green buildings.